Treatment of the macular edema in the course diabetic retinopathy and age–related macular degeneration - Stankiewicz, Andrzej; Spyra, Mariusz (Przewodnik Lekarza/Guide for GPs, 2012)
Macular edema is a very serious ophthalmological complication of diabetic retinopathy and age related macular degeneration, in consequence provided to decrease of visual acuity or practical blindness. The aim of study is to present actual management and treatment macular edema to preserve good vision of the patient. Actual trend in the treatment of macular edema in diabetic retinopathy and exudative age related macular degeneration is anti-VEGF therapy as intra vitreous injection, which in early stadium of disease gives possibility to stop process and improve visual acuity.